Effect of crop establishment and weed management in wheat (Triticum aestivum)-greengram (Vigna radiata) crop sequence - SHIVRAN, HANSRAJ; YADAV, R S; SINGH, S P; GODARA, A S; TOMAR, R (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted at SKRAU, Bikaner during 2016–18 comprising 28 treatments combinations havingfour crop establishment methods and seven weed management practices in a strip-plot design with four replicationsin wheat (Triticum aestivum L.) crop and its residual effect on succeeding greengram (Vigna radiata L.) crop wasobserved. Among crop establishment methods, stale seedbed (SSB)+ glyphosate 2.0 kg/ha significantly reduced thedry matter of weeds, viz. Chenopodium album, Rumex dentatus, Cyperus rotundus and Cynodon dactylon at all thestages, and increased the number of effective tillers, grain and straw yield of wheat to the tune of 8.02, 10.14 and 8.08,10.28 and 8.09, 10.85 percent (%) in comparison to deep and conventional tillage, respectively. Metsulfuron methyl4.0 g/ha + one hand hoeing registered the lowest dry matter of all the weeds except Cyperus rotundus and Cynodondactylon at 60 DAS and harvest and it also produced the maximum number of effective tillers (105.75), spike length(6.26 cm), grains per spike (38.53), grain yield (3354 kg) and straw yield (4403 kg) over other herbicidal treatments.In succeeding greengram crop the weed dry matter was not significantly affected due to crop establishment methodsexcept C. rotundus and C. dactylon. Yield of greengram was also not influenced by applied treatment in wheat.